Jagters vs Boere: n Soeke na die oorsprong van godsdiens - Jaco Beyers (Verbum et Ecclesia, 2012)
The question to the origin of religion is as old as the concept of religion itself. To understand religion, it helps to understand the categories of definitions for religion. There are several theories as to the evolutionary development of religion. Examples from Turkey as well as South Africa are used to illustrate that one model of explanation cannot be applied to all. This article wants to stress the importance of context when explaining the origin of religion. Each and every occurrence of religion has its own contextual explanation. What is however important is to recognise the universal human ability to recognise, accept and transfer religious concepts. This principle is illustrated by making use of the model of cognition in combination with other models.